Crystal structure of the Toll/interleukin‐1 receptor (TIR) domain of IL‐1R10 provides structural insights into TIR domain signalling. Issue 7 (1st February 2022) - Nimma, Surekha; Gu, Weixi; Manik, Mohammad K.; Ve, Thomas; Nanson, Jeffrey D.; Kobe, Bostjan
Abstract : The Toll/interleukin‐1 receptor (TIR) domains are key innate immune signalling modules. Here, we present the crystal structure of the TIR domain of human interleukin‐1 receptor 10 (IL‐1R10), also called interleukin 1 receptor accessory protein like 2. It is similar to that of IL‐1R9 (IL‐1RAPL1) but shows significant structural differences to those from Toll‐like receptors (TLRs) and the adaptor proteins MyD88 adaptor‐like protein (MAL) and MyD88. Interactions of TIR domains in their respective crystals and the higher‐order assemblies (MAL and MyD88) reveal the presence of a common 'BCD surface', suggesting its functional significance. We also show that the TIR domains of IL‐1R10 and IL‐1R9 lack NADase activity, consistent with their structures. Our study provides a foundation for unravelling the functions of IL‐1R9 and IL‐1R10. Abstract : This study presents the crystal structure of the Toll/interleukin‐1 receptor (TIR) domain of human interleukin‐1 receptor 10 (IL‐1R10), also called interleukin 1 receptor accessory protein like 2. It is similar to IL‐1R9 TIR (IL‐1RAPL1) but shows significant structural differences to TIR domains from Toll‐like receptors and the adaptor proteins MyD88 adaptor‐like protein and MyD88. We propose that the dimer observed in the IL‐1R10 TIR crystals represents a non‐signalling, auto‐inhibited form of the protein.